Australia's National Assessment Programme rubrics: An impetus for self-assessment?. Issue 1 (2nd January 2021) - Fletcher, Anna
ABSTRACT: Background : On an annual basis, students across Australia in Years 3, 5, 7 and 9 are assessed on their literacy and numeracy skills via the National Assessment Program – Literacy and Numeracy (NAPLAN), with the student performance data used for purposes including national accountability. Purpose : Against this backdrop of large-scale national assessment, this practitioner-research case study explored the possibilities of using existing NAPLAN writing assessment rubrics as a basis for formative assessment purposes. Specifically, the aim was to galvanise and encourage a culture of self-assessment within one school, using the notion of intelligent accountability. Sample : Participants included seven teachers and 126 students in Years 2, 4 and 6 (students aged approximately 7, 9 and 11 years), at an independent school in Northern Territory, Australia. Design and methods : The data presented here derive from a larger study which aimed to explore ways in which assessment can be used to scaffold students' ability to self-regulate their learning, as part of a classroom writing project. Data sources included planning templates, writing samples, interviews with students and teachers, and email correspondence with teachers. The data were analysed for emerging themes and interpreted within a framework of social cognitive theory. Findings : The analysis identified that students used the self-assessment process to set specific learning goals for developing a number of aspects of their writing. In terms of intelligent accountability, three elements of difference were distinguished: time, confidence and experience. Conclusions : The findings from this study highlight the crucial role of self-assessment within classroom practice. The researcher-practitioner self-assessment framework developed suggests the potential for utilising large-scale assessment rubrics as a basis for formative assessment activity.